Alteration of the gut microbiota after surgery in preterm infants with necrotizing enterocolitis - Lin, Huijia; Xu, Cuifang; Chen, Junjin; Ma, Xiaolu; Shi, Liping; Shi, Wei; Du, Lizhong; Ni, Yan (Frontiers in Pediatrics, 2023)
Purpose To investigate the dynamic changes in the intestinal microbiota in preterm infants with necrotizing enterocolitis (NEC) before and after treatment via a prospective case-control study. Methods Preterm infants with NEC and preterm infants with similar age and weight (control group) were enrolled in this study. They were divided into NEC_Onset (diagnosis time), NEC_Refeed (refeed time), NEC_FullEn (full enteral nutrition time), Control_Onset, and Control_FullEn groups according to the time of the fecal material collected. Except for basic clinical information, fecal specimens of the infants were obtained as well at indicated times for 16S rRNA gene sequencing. All infants were followed up after discharge from the NICU, and the growth data of the corrected age of 12 months were acquired from the electronic outpatient system and telephonic interviews. Results A total of 13 infants with NEC and 15 control infants were enrolled. A gut microbiota analysis showed that the Shannon and Simpson indices were lower in the NEC_FullEn group than in the Control_FullEn group (p < .05). Methylobacterium, Clostridium_butyricum, and Acidobacteria were more abundant in infants with NEC during diagnosis. Methylobacterium and Acidobacteria were remained plentiful in the NEC group until the end of treatment. These bacteria species were significantly positively correlated with CRP and negatively correlated with platelet count. The rate of delayed growth was higher in the NEC group than in the control group (25% vs. 7.1%) at 12 months of corrected age, but there was no significant difference. In addition, the pathways of synthesis and degradation of ketone bodies were more active in the NEC subgroups, including both the NEC_Onset group and the NEC_FullEn group. The pathway of sphingolipid metabolism was more active in the Control_FullEn group. Conclusion Even after reaching the full enteral nutrition period, alpha diversity in infants with NEC who underwent surgery was lower than that in the control group infants. It may take more time to reestablish the normal gut flora of NEC infants after surgery. The pathways of the synthesis and degradation of ketone bodies and sphingolipid metabolism might be related to the pathogenesis of NEC and physical development after the occurrence of NEC.